Development and evaluation of functional biscuits infused with functional spices and white pea flour: A comprehensive study on optimizing glycemic control and incorporating anti-diabetic additives - Minhaj Uddin; Nabil Mashahid; Juairia Absar Anta; Mahima Ranjan Acharjee (Applied Food Research)
The present study aimed to develop a functional biscuit incorporating ingredients with potential anti-diabetic properties, tailored to support glycemic control as part of a balanced diet. Three formulations (A, B, and C), along with a control, were prepared by replacing 16 % of wheat flour with white pea flour. The formulations were further differentiated by the addition of 5 g of ginger powder (sample A), fenugreek seed powder (sample B), and cinnamon powder (sample C), all known for their potential to improve insulin sensitivity and lower blood sugar levels. Proximate composition analysis revealed significant differences among the samples and control (p < 0.05). Sample B exhibited the highest moisture (10.34 ± 0.13 %), protein (16.22 ± 0.12 %), and fiber (3.79 ± 0.01 %) content. Sample A had the lowest total sugar content (4.70 ± 0.03 %). Mineral analysis showed a reduction in sodium from 62.41 ± 0.06 mg/100 g in the control to 58.23 ± 0.02 mg/100 g in sample C, while potassium increased from 136.42 ± 0.20 mg/100 g in the control to 158.62 ± 0.02 mg/100 g in sample A. Calcium content increased from 310.21 ± 0.02 mg/100 g in the control to 465.34 ± 0.38 mg/100 g in sample B. The total phenolic content (TPC), total flavonoid content (TFC), and antioxidant capacity were highest in sample A (3.276 ± 0.295 mg GAE/100 g), sample B (63.693 ± 0.321 mg QE/100 g), and sample C (1.219 ± 0.153 %), respectively. Sample C also exhibited the lowest IC50 value (52.75 ± 0.12 ppm), indicating the highest α-amylase inhibitory activity. Sensory evaluation showed that sample A was the most acceptable. The biscuits show potential as diabetic-friendly snacks, aiding in blood sugar management and overall health.